Analisis Pemanfaatan Sistem Preservasi Arsip Web Indonesia Menggunakan Technology Acceptance Model Studi Kasus Pada Perpustakaan Nasional RI - Novi Murdiyanti; Irman Hermadi; Joko Santoso (Perpustakaan IPB, 2016)
Web as a source of global information has created a new challenge for archiving digital material. National Web Archive as one part of the web portal of the National Digital Library has an important role in the effort to store, manage, archive and preserve the documentary heritage of Indonesia in online formats. This study was done to evaluate the utilization of associated factors that interact and influence the level of user acceptance of the technology of this web archiving system. The study using the modeling methodology TAM (Technology Acceptance Model) as a theoretical framework and multivariate statistical analysis techniques SEM (Structural Equation Modeling) using AMOS (Analysis of Moment Structures) software tools. Data were collected through snowball sampling with the help of an online questionnaire, where the number of 110 respondents in this study are pemustaka who utilize the site of the National Library. The results show the suitability of TAM as a theoretical framework that can accept the hypothesis that has positive and significant exception Influence Perception of Benefits (PU) on Intention to Use (BITU) indicates a value below 0.736 because of the measurement standard price table = 1.96 ie thitung <ttable so H0 is accepted.Keywords: web archive, Technology Acceptance Model, Structural Equation Modeling.